Evaluación del poder patogénico de Cytospora chrysosperma en clones de chopo - Alonso, D.=700 1 Pajares, J.; Diez, J.
Resumenes (Es, En)
5 fotos; 9 ref.
Keywords: CYTOSPORA; POPULUS; CYTOSPORA CHRYSOSPERMA; CHOPO; NECROSIS DEL FLOEMA DE LOS CHOPOS